NARASI KEKERASAN SIMBOLIK DAN MELEMBAGA DALAM NOVEL TEROR MORAL KARYA ONGKY ARISTA UA - milliana milliana (BASA Journal of Language & Literature, 2022)
Symbolic violence is a way that is always used by the dominant class or upper class in the social structure (ma-institutional) of society to impose. mindset,culture, also the lifestyle of the lower class. The focus of this research is on how the form of symbolic violence in the novel Moral Terror, how the institutional character in the novel Moral Terror. This research is a qualitative descriptive research with the main instrument in the research being the researcher. Alone. The purpose of this study is to describe the symbolic violence and institutionalized violence that occurs in the novel Terror Moral by Ongky Arista UA. The focus of the research is 1) violence. symbolic includes the mechanism of euphemism; in the form of twelve. love, giving, and rejection. While the sensorization mechanism; in the form of preservation of positive morals, honor, and decency. 2) institutionalized violence includes social habitus mechanisms found in coastal island communities; in the form of upper class habitus, lower class habitus.